A 52-Year-Old Man With Progressive Weakness and Incontinence. (April 2022) - Altintas, Ayse; Danyeli, Ayca Ersen; Bozkurt, Subutay Berke; Uysal, Sanem Pinar; Akpek, Sergin; Aygun, Murat Serhat; Akay, Olga Meltem; Kahyaoglu, Bulent; Peker, Selcuk; Ure, Umit Barbaros; Ferhanoglu, Burhan
Here we report a challenging case of a 52-year-old man presenting with subacute constipation, urinary retention, impotence, absent Achilles reflexes, and hypoesthesia in S2-S5 dermatomes. We review the clinical decision-making as the symptoms evolved and diagnostic testing changed over time. Once the diagnosis is settled, we discuss the sign and symptoms, additional diagnostic tools, treatment options and prognosis.